Effect of Heavy Metal Stress on Phenolic Compounds Accumulation in Winter Wheat Plants - Marta Jańczak-Pieniążek; Jan Cichoński; Patrycja Michalik; Grzegorz Chrzanowski (Molecules, 2022)
Heavy metal stress can lead to many adverse effects that inhibit cellular processes at various levels of metabolism, causing a decrease in plant productivity. In response to environmental stressors, phenolic compounds fulfill significant molecular and biochemical functions in plants. Increasing the biosynthesis of phenolic compounds in plants subjected to heavy metal stress helps protect plants from oxidative stress. A pot experiment was carried out to determine the effect of the accumulation of copper (Cu) and lead (Pb) salts at concentrations of 200, 500, and 1000 ppm on seed germination, the activity of enzymes in the phenylalanine ammonia-lyase pathway (PAL) and tyrosine ammonia-lyase (TAL), along with the total phenol and flavonoid contents in seedlings of hybrid Triticum aestivum L. (winter wheat) cultivars. The accumulation of heavy metals, especially Cu, had a negative impact on the seed germination process. The cultivar “Hyacinth” reacted most strongly to heavy metal stress, which was confirmed by obtaining the lowest values of the germination parameters. Heavy metal stress caused an increase in the activity of PAL and TAL enzymes and an increase in the accumulation of phenolic compounds. Under the influence of Cu, the highest activity was shown in cv. “Hyvento” (especially at 200 ppm) and, due to the accumulation of Pb, in cv. “Hyacinth” (1000 ppm) and cv. “Hyking” (200 ppm). The cultivar “Hyking” had the highest content of phenolic compounds, which did not increase with the application of higher concentrations of metals. In other cultivars, the highest content of total phenols and flavonoids was usually observed at the lowest concentration (200 ppm) of the tested heavy metals, Cu and Pb.